2021
DOI: 10.1186/s40729-021-00388-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of alternative or adjunctive measures to conventional non-surgical and surgical treatment of peri-implant mucositis and peri-implantitis: a systematic review and meta-analysis

Abstract: Purpose To evaluate the efficacy of alternative or adjunctive measures to conventional non-surgical or surgical treatment of peri-implant mucositis and peri-implantitis. Material and methods Prospective randomized and nonrandomized controlled studies comparing alternative or adjunctive measures, and reporting on changes in bleeding scores (i.e., bleed0ing index (BI) or bleeding on probing (BOP)), probing depth (PD) values or suppuration (SUPP) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
108
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 115 publications
(348 reference statements)
9
108
0
Order By: Relevance
“…Four systematic reviews analyzed the use of APWJT during active peri-implant therapy [7,39,41,45]. All of the included studies used glycine as an air polishing powder.…”
Section: Active Peri-implant Mucositis/peri-implantitis Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Four systematic reviews analyzed the use of APWJT during active peri-implant therapy [7,39,41,45]. All of the included studies used glycine as an air polishing powder.…”
Section: Active Peri-implant Mucositis/peri-implantitis Therapymentioning
confidence: 99%
“…When APWJT was used as an alternative to conventional methods in the treatment of peri-implant mucositis, it was concluded that both treatment methods resulted in comparable clinical outcomes [7,39,41]. Just one study performed a meta-analysis that resulted in contradictory results, showing an additional benefit of APWJT regarding PPD reduction in the treatment of peri-implant mucositis [39].…”
Section: Active Peri-implant Mucositismentioning
confidence: 99%
See 1 more Smart Citation
“…Even though clinical parameters can be improved by mechanical debridement (MD), sites with deeper pockets and BOP are still observed after the treatment (Heitz‐Mayfield et al, 2011). Ancillary methods, including the use of mouthwash, application of local antiseptic gel, use of antimicrobial photodynamic therapy, systemic antibiotics, and air abrasion device, have not provided additional benefits when compared with conventional mechanical treatment (Ciancio et al, 1995; Porras et al, 2002; Lindhe & Meyle, 2008; Thone‐Muhling et al, 2010; Heitz‐Mayfield et al, 2011; Hallström et al, 2012; Jepsen et al, 2015; Albaker et al, 2018; Barootchi et al, 2020; Liu et al, 2020; Ramanauskaite et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many treatment options have been proposed during the years in areas affected by peri-implantitis [ 14 ]. It is widely accepted that mild cases should be treated non-surgically; this approach is also recommended as the initial phase for severe cases.…”
Section: Introductionmentioning
confidence: 99%